Kajian Tingkat Kinerja Pegawai - Zuriana Zuriana; Linda Septarina; Ima Andriyani (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
ABSTRACT Research to determine the level of employee performance was carried out at SMA N 1 Katibung and SMA N 1 Sragi, South Lampung Regency. The level of employee performance is proxied by a comparison of employee performance in this case teachers by age. The type of research used is quantitative with a comparative method. The researchers used a population of teachers from SMA N 1 Katibung and SMA N 1 Sragi as many as 78 teachers and a set sample of 34 honorary teachers. The sample is divided into teachers with an old age category of 18 honorary teachers and teachers in the young age category of 16 honorary teachers. The sampling technique uses purposive sampling techniques and independent t-Test data analysis. The result of this study is that there are differences in the performance of employees or teachers in the old age category and teachers with the young age category at SMA N 1 Katibung and SMA N 1 Sragi Lampung Selatan.